Transport Stirrup Jars of the Bronze Age Aegean and East Mediterranean - Jones, Richard E. (EBL-Schweitzer, 2011)
List of Illustrations in the Text; List of Tables; List of Graphs; List of Figures; List of Plates; Acknowledgments; List of Abbreviations; 1Introduction; 2 Typology; 3 Scientific Backgound and Aims of the Analyses; 4 Chemical Analyses; 5 Petrographic Analyses; 6Interpretation of the Chemical and Petrographic Data; Chemistry, Petrography, and Typology: Geographical Associations; 8The Linear B Inscriptions; 9Chronology and Power; 10Trade; 11Catalog; Appendix; References; Concordance 1; Concordance 2; Index; General Index